Pengembangan LKPD Berbasis Literasi Sains Tema 9 Menjelajah Angkasa Luar Untuk Kelas VI SDN 6 Ulu Musi Kabupaten Empat Lawang - M. Dou Boys Pernandes Pernandes; Endang Widi Winarni; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
This study aims to develop LKPD based on scientific literacy. The type of research used is research and development (R & D) modifying by the Sugiyono model adopting 6 steps, namely analysis, planning, design, validation, revision, and testing. The research data were obtained through questionnaires, interview guidelines, validation sheets, and student response questionnaires. The validated aspects include the feasibility of the material, language, presentation and graphics involving 6 validators consisting of experts and practitioners. Validation data were analyzed using the Aiken'V formula and reliability. Data on student responses to LKPD were obtained from the responses of 15 students in class VI. The data is in the form of 'yes' 'no' data which is analyzed by Guttman's theory. Based on the results of research and development, it is concluded that scientific literacy-based worksheets are very suitable to be used in learning Tema 9 Menjelajah Angkasa Luar for class VI SDN 6 Ulu Musi, Kabupaten Empat Lawang.